Penerapan Corporate Social Responsibility (CSR), Antara Tantangan dan Tuntutan - Barthos, Megawati; Nugraha, Lingga; Sukendar Situmorang, Suhadi; Situmeang, Ojak (Pascasarjana UDA, 2023)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR) in Indonesia, focusing on the economic, social, and environmental dimensions that form the basis for CSR policies in this country. This study also explores the challenges faced in implementing CSR policies, as well as the factors that support and inhibit the implementation of CSR by companies. In this study, it was found that although there are regulations governing CSR, the main challenge lies in the lack of clarity of policies and the mismatch between the expectations of the community, companies, and the government. Supporting factors such as organizational culture and customer demand greatly influence the success of CSR implementation. Conversely, inhibiting factors such as minimal synchronization between the government and the business world and the lack of clear technical guidelines are significant obstacles to effective implementation. Therefore, more integrated policies and collaboration between the government, companies, and the community are needed to improve the implementation of CSR that has a positive impact on social and environmental sustainability.